Pengambilan Keputusan Perusahaan dalam Kebijakan Dividen - Njotoprajitno, Rosemarie Sutjiati (Zenit, 2013)
In this era, optimalization of company value represented by stock value has become the main purpose of company management. Dividend policy is directly connected to this matter. Continuous shared dividend may or may not attract potential investors depending on their purpose of investment. The option to retain earning also may lead to different results. Stock price may escalate or drop depending on the policy made. This paper tries to examine and discuss this matter as well as tries to search the best possible policies regarding the dividend policy. This paper follows the general views that dividend policy does effect the stock price and disagreeswith Modigliani Miller’s view which needs a lot of assumptions irrelevant to the real world.Keywords: Stock price, dividends, dividend policy, retain earning.